Can We Make Punjab Thalassemia Free? - Bhardwaj K; Kanchan Bhardwaj (GMC Patiala Journal of Research and Medical Education, 2018)
Thalassemia is the single most common gene defect and poses a major health burden in Punjab especially in Khatris & Aroras. There are about one lakh children with â Thalassemia syndrome in India with over 10,000 new thalassemia major children born in India every year. There are about 68 â Thalassemia mutations described in India, the knowledge of which can help in prenatal diagnosis.CBC or NESTROFT can be used as a screening tool for differentiating Thalassemia trait from iron deficiency anaemia. HbA estimation is 2 the gold standard in carrier screening however final diagnosis is done by DNA studies. Evaluation for organ dysfunction from time to time is must for early detection of complications and their prompt treatment. Preventing the birth of thalassemia major child is essential. Key Words: â -Thalassemia major, â-Thalassemia minor/ Thalassemia carrier/ trait, , Molecular genetics of â-Thalassemia, Prenatal diagnosis of thalassemia, Blood transfusion, Iron Chelation, Bone marrow hematopoietic stem cell transplantation, Stem cell registry, Hydroxyurea.